2011
DOI: 10.1039/c1ce05181d
|View full text |Cite
|
Sign up to set email alerts
|

EDTA-mediated hydrothermal synthesis of NaEu(MoO4)2 microrugbies with tunable size and enhanced luminescence properties

Abstract: Tetragonal NaEu(MoO 4 ) 2 with rugby-like microstructures were successfully synthesized by a hydrothermal method in an EDTA-mediated process. X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and high resolution transmission electron microscopy (HRTEM) techniques were employed to characterize the products in detail. It was found that the amount of EDTA, reaction temperature and pH value are important parameters affecting the morphology, crystallinity and size o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 44 publications
0
65
0
1
Order By: Relevance
“…Enlightened by the above experimental results and the previous report [8,13,26], a stepwise ''fast crystallizationdissolution-recrystallization'' growth mechanism can be proposed for the formation of NaSm(MoO 4 ) 2 crystals. It is noteworthy that the appropriate amount of citric acid is a prerequisite for the formation of such submicro-crystals.…”
Section: Formation Mechanism Of the Nasm(moo 4 ) 2 Crystalsmentioning
confidence: 80%
See 4 more Smart Citations
“…Enlightened by the above experimental results and the previous report [8,13,26], a stepwise ''fast crystallizationdissolution-recrystallization'' growth mechanism can be proposed for the formation of NaSm(MoO 4 ) 2 crystals. It is noteworthy that the appropriate amount of citric acid is a prerequisite for the formation of such submicro-crystals.…”
Section: Formation Mechanism Of the Nasm(moo 4 ) 2 Crystalsmentioning
confidence: 80%
“…It was reported that the pH value of the precursor solution could effectively affect the balance between the chemical potential and the rate of ionic migration in the precursor solution, and hence the morphology and size of the products [13]. In the present case, for NaSm(MoO 4 ) 2 crystals, a low pH value results in a fast crystal growth, and hence a large crystal size (Fig.…”
Section: Effect Of the Ph Valuementioning
confidence: 80%
See 3 more Smart Citations